DOHA ROUND OF WTO AND AFRICAN DEVELOPMENT: AN APPRAISAL - Duruji, Moses M.; Olarenwaju, Faith; Azuh, Dominic E.; Joshua, Segun (European Scientific Journal, ESJ, 2014)
World Trade Organization (WTO) emerged in 1994 to create global environment for free and unhindered trade. The believe was anchored on the fact that global cooperation will foster world peace through trade liberalization and reduction of the powers of domestic special interests through broad rules that cuts across national frontiers. These were hinged on the idea that greater cooperation through trade liberalization will promote common good on a global scale. In as much as this global trading system has benefited industrial societies who constitute the inner caucus of WTO, the same cannot be said of developing countries especially the states of Africa. One area that has been glaring is liberalization of agriculture which analyst agrees would give developing countries competitive advantage and offer those countries at the margin, greater share of world trade with significant impact on the development agenda of those countries. Good as this sound, it has been most difficult to achieve liberalization of trade in agriculture and the reason rests on the huge subsidies industrialised countries spends to augment their farmers which creates an imperfect market that is detrimental to developing countries. The paper examined the ways in which WTO has handled its fundamental objectives as it relates to the issues surrounding the Doha Round of talks which was dedicated to achieve liberalization of agriculture. The paper concluded that developing countries especially those in Africa have continued to loose out as a result of the inconsiderate stance of developed countries to maintain the global imperfect market structure, thus stalling an avenue that would have jump started Africa development.